Kajian Indoor Air Quality pada Rumah Tradisional Baileo Pegunungan di Seram Bagian Barat, Maluku - Felicia Jane Thendean; Purnama Esa Dora Tejokeosumo; Anik Rakhmawati (Intra, 2019)
Indoor Air Quality (IAQ) is an aspect that greatly affects the health and comfort of room users. Indoor Air Quality (IAQ) is influenced by physical factors (temperature, air humidity and air velocity) and chemical factors in the form of substances such as HCHO and TVOC in the air. Indoor Air Quality (IAQ) has actually been applied since a long time ago in traditional buildings such as Baileo . The study used a comparative quantitative method on Baileo in the mountainous area with the aim of reviewing and comparing Indoor Air Quality (IAQ) on Baileo and building formations to materials used as references in future designs. Indoor Air Quality (IAQ) in mountain Baileo in West Seram is good where temperature, air humidity, air velocity and TVOC and HCHO substances in the room do not exceed the threshold value (NAB) which adversely affects the health and safety of room users.